Midwifery Care Management for Pregnant Women in Mrs. “R” Gestation 20-22 Weeks With Mild Anemia At Mamajang Health Center, June 07- august 2, 2024 - Yayu, Sriwahyuni; Firdayanti, Firdayanti; Taherong, Ferawati; Diarfah , Andi Dian; Andryani, Zelna Yuni (Jurnal Midwifery, 2026)
Introduction Mild anemia in pregnant women with Hb ≥11 Gr/dl The impact of mild anemia can be moderate to severe anemia in pregnancy, can be fatal if not immediately addressed such as causing miscarriage, premature labor, uterine inertia, prolonged labor, uterine atony, and bleeding and shock. The World Health Organization (WHO) states that globally the prevalence of pregnant women who experience anemia is 83.2% while in Southeast Asia the prevalence is 97.8%. This shows that the prevalence of anemia in Southeast Asia exceeds the global prevalence value. From the data above, it indicates that anemia in pregnant women is one of the important risk factors in health. Research Methods This study aims to implement midwifery care for pregnant women in Mrs. "R" with mild anemia based on midwifery care management. The method applied in this study is using the 7-step Varney analysis. Case Study Results Mrs. "R" With mild anemia for 8 weeks, anamnesis was conducted through interviews by asking about patient complaints, monitoring vital signs, supporting Hb examinations and taking care measures by advising the mother to maintain adequate diet and rest and recommending routine consumption of iron tablets during pregnancy. The conclusion of the case study of Mrs. "R" was a visit at 8 weeks, the results showed that the mother's condition was good, with no dizziness, vital signs within normal limits and Hb within normal limits where previously 9.3 Gr / dl became 11.9 Gr / dl and no potential problems occurred. So in the documentation that has been done on Mrs. "R" there is no theoretical gap.